Sustainability of agribusinesses through an integrated circular economy model - Rodriguez Yparraguirre, Abel Jose (2025)
In the context of current challenges to achieving sustainable development, the circular economy emerges as a viable alternative to transform traditional production processes. This study evaluated the impact of a circular economy model on an agricultural enterprise, using a mixed-methods approach that combined qualitative and quantitative analysis of sustainability indicators. The sample consisted of the company’s internal processes, employing techniques such as documentary analysis, direct observation, and simulation. The results indicated a 95% plant survival rate, with an average annual fruit yield of 5 kg, limited by soil fertility and irrigation issues. Following the implementation of the circular model, productive land increased from 35% to 50%, access to freshwater improved from 25% to 40%, and the efficiency in the use of material and energy resources rose from 45% to 60%. Additionally, there were improvements in personnel knowledge (from 65% to 75%), team health (from 60% to 70%), manufacturing capacity (from 50% to 65%), and financial health (from 55% to 70%). In summary, the model significantly contributed to the environmental, economic, and social strengthening of the company, highlighting the importance of integrating such practices into business policies to advance sustainable development.